Agricultura camponesa no Curimataú Paraibano: entre a subsistência e a sustentabilidade socioambiental - Sá Sobrinho, Rosivaldo Gomes de (2010)
This work intends to understand the environmental and social relationships shaped by the peasants from micro region Curimataú of Paraiba State. Here it is stated that the challenges posed both by the social relationships as soon as the environmental conditions stimulate these peasants to establish or reinvent strategies that allow them to go on living and producing. In order to support arguments, this work dialogues with different theoretical views from Rural Sociology and it is based on the perspective of coping with semiarid region and "the poor people environmentalism". The aim of this work is to understand the struggle for maintaining the peasant´s way of living as a significant contribution for the conservation of the natural resources which still exist in the micro region studied. Peasants inserted in the global society, even while remaining relatively autonomous to the market, create productive strategies which have enabled them to cope with the semiarid region conditions, and thus, they offer to society a number of elements by which one can question the priorities of major development policies that are proposed for this region historically known by incentives to extensive agriculture and livestock. The different strategies for coping with semiarid region reveal the irrationality of development policies, which guided by the ambition of the productivity gains, they neglected the social and environmental conditions features of a predominantly smallholders region. However, even outside of these policies, the peasants from Curimataú go on playing their way of living and showing new paths and semiarid region development perspectives, by basing on the coping with semiarid region. From this perspective, peasants guide their actions by the interaction between the family needs fulfillment and the natural resources maintenance that is considered here as an example of "the people poor environmentalism". Looking at this reality from the socio and environmental perspectives allows us to state that the maintenance of this way of living is associated with practices of environmental conservation and thus helps us to reflect on new development possibilities. Guided by a rationality that is oriented by the family and environmental maintenance, these peasants shape a new paradigm of rural development, by associating agricultural practices involving non-agricultural occupations that enables us to say that this place, the countryside, is not only a space of production, but rather a place of life and conservation. The set of practices that enable the peasant maintenance is essential to the conservation of biodiversity to which this way of living is intrinsically linked. The formulation of strategies such as plate tanks, underground dams, stone tanks, seed banks, knowledge on plants and on the environmental potential demonstrate how it is possible to construct a new focus on the semiarid region and its population. These observations allow reflect on the importance and the strategic location that the peasant family farming has occupied in the shaping of the development and sustainability of the Brazilian semiarid region